Relationship Between Reading Interest and Indonesian Language Learning Outcomes of Grade IV Elementary School Students - Monipo, Yulan; Wilade, Surahman; Aqil, Moh.; Rizal, Rizal; Lapasere, Sisriawan (Papanda Publisher, 2025)
Reading interest plays a crucial role in academic achievement, particularly during elementary education when foundational literacy skills are established. However, limited research has examined this relationship within Indonesian elementary education contexts. This study investigated the correlation between reading interest and Indonesian language learning outcomes among fourth-grade students. A quantitative correlational design was employed with 16 fourth-grade students at SD Inpres 5 Taipa Laga selected through simple random sampling. Data were collected using a validated 13-item reading interest questionnaire (Cronbach's α = 0.85) and students' midterm examination scores in Indonesian language. Statistical analysis was conducted using Pearson's correlation with significance set at p ≤ 0.05. All participants demonstrated either high (44%) or very high (56%) reading interest levels. Academic performance showed similar distribution with 44% achieving good scores and 56% excellent scores. Correlation analysis revealed a statistically significant positive relationship between reading interest and learning outcomes (p = 0.003). Students with very high reading interest achieved excellent academic performance (88.9%) compared to those with high interest (14.3%). The findings validate Expectancy-Value Theory by demonstrating how intrinsic motivation correlates with academic achievement. Results align with previous research emphasizing the importance of reading interest in literacy development. The strong correlation suggests that educational interventions targeting reading interest cultivation may enhance academic outcomes. Study limitations include small sample size and cross-sectional design, necessitating longitudinal research with diverse populations to establish causal relationships.